Evaluación de un protocolo de multiplicación IN VITRO DE CANNABIS SP. en condiciones controladas en el cantón Latacunga. - Pacheco Oñate, Erika Viviana (2024)
In this research an in vitro multiplication protocol for Cannabis sp. was developed for growing and obtention of new varieties. In stage 1 germination percentage of different landraces was evaluated in vitro and using peat. In stage 2 germinated achenes were subcultured in peat plus 6-benzyl amino purine (6-BAP), macro and micronutrients; and in stage 3 the process for in vitro multiplication of shoots was optimized. Landraces CRNTIO, M.B., and V.P., as well as culture medium GENNBIO were used. Treatments were evaluated using percentages, and quantitative characters were analysed among landraces through analysis of variance (ANOVA). The percentage of in vitro germination for M.B. = 32%, followed by CNRTIO = 16%, and using peat P.V. = 8%, and M.B. = 93.75%. In stage 2 the number of leaves (mean) was statistically different between P.V. = 14 and M.B. = 10.67; the explant length (cm), and the number of shoots were similar between P.V. and M.B. In stage 3 significant differences were obtained for number of shoots or leaves (mean ± S.E.) between P.V. = 1.70 ± 0.51 and M.B. = 0.00 ± 0.51, also for explant length (mm) between P.V. = 2.00 ± 0.57 and M.B. = 0.00 ± 0.57; and in CRNTIO2 was observed callogenesis response in presence of kinetin in the selected medium. The impact of this approach is the development of an efficient protocol for shoot multiplication, and regeneration of hemp plantlets to be genetically transformed, and conserved in germplasm banks for industrial uses in Cotopaxi-Ecuador.